1999
DOI: 10.1021/jm990234x
|View full text |Cite
|
Sign up to set email alerts
|

Selective A3 Adenosine Receptor Antagonists:  Water-Soluble 3,5-Diacyl-1,2,4-trialkylpyridinium Salts and Their Oxidative Generation from Dihydropyridine Precursors

Abstract: A(3) adenosine receptor antagonists are sought for their potential antiinflammatory, antiasthmatic, and antiischemic properties. We have found that 3,5-diacyl-1,2,4-trialkyl-6-phenylpyridinium derivatives constitute a novel class of selective A(3) adenosine receptor antagonists. The structure-activity relationships of this class of antagonists, incorporating the 3-thioester, have been explored. The most potent analogue in this group was 2, 4-diethyl-1-methyl-3-(ethylsulfanylcarbonyl)-5-ethyloxycarbonyl -6-phe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…General SAR of pyridine derivatives revealed that structural requirements responsible for enhancement of A 3 AR affinity and selectivity did not completely reflect that of the DHP parent compounds . Among this series, were also reported fluorinated and hydroxylated pyridine derivatives and an extension of this study performed by Jacobson and co‐workers described a series of N ‐alkylpyridinium salts as water soluble A 3 AR antagonists although with lower potency than the pyridine analogues . A pyridine‐based A 3 AR antagonist PET ligand [ 18 F]FE@SUPPY was introduced …”
Section: Medicinal Chemistry Of the A3 Adenosine Receptormentioning
confidence: 99%
“…General SAR of pyridine derivatives revealed that structural requirements responsible for enhancement of A 3 AR affinity and selectivity did not completely reflect that of the DHP parent compounds . Among this series, were also reported fluorinated and hydroxylated pyridine derivatives and an extension of this study performed by Jacobson and co‐workers described a series of N ‐alkylpyridinium salts as water soluble A 3 AR antagonists although with lower potency than the pyridine analogues . A pyridine‐based A 3 AR antagonist PET ligand [ 18 F]FE@SUPPY was introduced …”
Section: Medicinal Chemistry Of the A3 Adenosine Receptormentioning
confidence: 99%
“…A prodrug scheme for the oxidative generation of pyridinium salts which act as antagonists of the human A 3 AR from the corresponding 1-alkyldihydropyridine derivatives. Such antagonists are highly watersoluble in contrast to most other classes of A 3 AR antagonists, which are hydrophobic [Xie et al, 1999].…”
Section: Pyransmentioning
confidence: 99%
“…5) constituted a novel class of selective A 3 AR antagonists of moderate affinity [Xie et al, 1999]. The SARs of this class of antagonists, incorporating the 3-thioester, were explored.…”
Section: Pyridinium Salts -Activated From Prodrugs Through Oxidationmentioning
confidence: 99%
“…A specific subset of agonists and antagonists against hA 3 AR has been selected basing on their potency and selectivity profiles, maximizing as much as possible their chemical diversity [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. The selected ligands are shown in Figures 2 and 3.…”
Section: Agonists and Antagonists Selectionmentioning
confidence: 99%